"Children get sick all the time": A qualitative study of socio-cultural and health system factors contributing to recurrent child illnesses in rural Burkina Faso. (December 2016) - Østergaard, Lise; Bjertrup, Pia; Samuelsen, Helle
Abstract Background In Burkina Faso, the government has implemented various health sector reforms in order to overcome financial and geographical barriers to citizens' access to primary healthcare throughout the country. Despite these efforts, morbidity and mortality rates among children remain high and the utilization of public healthcare services low. This study explores the relationship between mothers' intentions to use public health services in cases of child sickness, their social strategies and cultural practices to act on these intentions and the actual services provided at the primary health care facilities. Focusing on mothers as the primary caregivers, we follow their pathways from the onset of symptoms through their various attempts of providing treatment for their sick children. The overall objective is to discuss the interconnectedness of various factors, inside and outside of the primary health care services that contribute to the continuing high child morbidity and mortality rates. Methods The study is based on ethnographic fieldwork, including in-depth interviews and follow-up interviews with 27 mothers, informal observations of daily-life activities and structured observations of clinical encounters. Data analysis took the form of thematic analysis. Results and discussion Focusing on the mothers' social strategies and cultural practices, three forms of responses/actions have been identified: home-treatment, consultation with a traditional specialist, and consultation at the primary health care services. Due to theiraccumulated vulnerabilities, mothers shift pragmatically from one treatment to another. However, the sporadic nature of their treatment-seeking hinders them in obtaining long-term solutions and the result is recurrent child illnesses and relapses over long periods of time. Theroutinization of the clinical encounter at rural dispensaries furthermore fails to address these complexities of children's illnesses. Conclusions The analysis of case studies, interviews and observations shows how mothers in a rural area struggle and often fail to receive care at public healthcare facilities. Health service delivery could be organized in a manner that responds better to the needs of these mothers in terms of both access and retention.